Visual Style and the Cultural Representation of Islam in Penginyongan Film: An Analysis of Banyumas Raya Indonesia Cultural Expression - Ferdinanda Ferdinanda; Guntur Guntur; Ranang Agung Sugihartono (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article examines how the Penginyongan film represents Islamic cultural values within the socio-cultural context of the Banyumas Raya community, Indonesia. The urgency of this research lies in the lack of studies that position local audio-visual media as a space for the articulation of religious values ​​and cultural identity amidst the penetration of digital modernity. Through a visual ethnography approach, this research not only utilizes field observations, interviews, and focus group discussions, but also conducts film text analysis to examine how social, cultural, and religious representations are constructed visually and narratively in four films: Pegatan (2023), SETAN: Seni Tani (2023), Dolanan Layangan (2020), and PUR (2024). The research findings show that Islamic cultural values are manifested through an egalitarian, simple visual style, a non-hierarchical communal production pattern, the use of the Ngapak language as a symbol of resistance and pride in local identity, and humor as a medium for polite social criticism. On the other hand, the Penginyongan film shows the dialectic between modernity and communality, especially amid changes in the lifestyles of the younger generation and the pressures of digital culture. This research contributes to strengthening the study of Indonesian local culture while broadening understanding in global cultural studies of how local communities negotiate religious values and cultural identity through short films. The cinema Penginyongan shows that cultural da'wah can be present through social ethics and everyday aesthetics, rather than through formal ritual symbols.